The Effectiveness of Online-Based Psychoeducation in Improving Family Caregivers' Ability to Care for Schizophrenia Patients: A Scoping Review - Darsana, I Wayan; Swarjana, I Ketut; Rahayuni, IGA Rai; Putra, I Putu Gde Yudara Sandra (Babali Publisher, 2025)
Introduction: Schizophrenia patients require lifelong care, which necessitates the family's ability to provide that care. Efforts to enhance the family's ability are carried out by giving psychoeducation to improve the skills of caring for schizophrenia patients. The problem with providing psychoeducation directly is that distance and time become obstacles; an effective, efficient, and easily accessible method can be achieved by utilizing information technology through online media. This scoping review aimed to identify the effectiveness of online psychoeducation in enhancing the ability of families to care for patients with schizophrenia. Methods: This scoping review used the PICO framework to develop article questions. (P: family of schizophrenia patients, I: psychoeducation, C: online and offline, and O: family's ability to care for schizophrenia patients). The databases were PubMed, ScienceDirect, and Google Scholar. The selected articles were published in the last 5 years, from 2019 to 2024. The keywords were used